Effect of water-containing acetone–butanol–ethanol gasoline blends on combustion, performance, and emissions characteristics of a spark-ignition engine. (1st June 2016) - Li, Yuqiang; Nithyanandan, Karthik; Lee, Timothy H.; Donahue, Robert Michael; Lin, Yilu; Lee, Chia-Fon; Liao, Shengming
Highlights: Water-containing ABE (acetone–butanol–ethanol) was used an alternative fuel. Water-containing ABE and gasoline blends were investigated in an SI engine. Water-containing ABE and gasoline blends can enhance engine torque. Water-containing ABE and gasoline blends can reduce CO, UHC and NOx emissions. Abstract: Bio-butanol has proved to be a promising alternative fuel in recent years; it is typically produced from ABE (acetone–butanol–ethanol) fermentation from non-edible biomass feedstock. The high costs for dehydration and recovery from dilute fermentation broth have so far prohibited bio-butanol's use in internal combustion engines. There is an interesting in studying the intermediate fermentation product, i.e. water-containing ABE as a potential fuel. However, most previous studies covered the use of water-containing ABE–diesel blends. In addition, previous studies on SI engines fueled with ABE did not consider the effect of water. Therefore, the evaluation of water-containing ABE gasoline blends in a port fuel-injected spark-ignition (SI) engine was carried out in this study. Effect of adding ABE and water into gasoline on combustion, performance and emissions characteristics was investigated by testing gasoline, ABE30, ABE85, ABE29.5W0.5 and ABE29W1 (29 vol.% ABE, 1 vol.% water and 70 vol.% gasoline). In addition, ABE29W1 was compared with gasoline under various equivalence ratios ( Φ  = 0.83–1.25) and engine loads (3 and 5 bar BMEP). It was found that ABE29W1 generally had higher engine toque (3.1–8.2%) and lower CO (9.8–35.1%), UHC (27.4–78.2%) and NOx (4.1–39.4%) than those of gasoline. The study indicated that water-containing ABE could be used in SI engines as an alternative fuel with good engine performance and low emissions.